TECHNOLOGICAL DIVERSIFICATION OF PROMOTING SPIRITUAL AND EDUCATIONAL ACTIVITIES IN THE LIVES OF 21ST CENTURY YOUTH - Pardayev Sobit Abdivali o‘g‘li; Raxmonov Jafar Nabi o‘g‘li (PEDAGOGS, 2025)
Annotation: Explains the technological approach to the implementation of propaganda and counter-propaganda work among young people and the positive impact on the minds of young people and highlights the essence of the ongoing renewal process in Uzbekistan; formation of devotion to our national customs and traditions; formation of social skills and competencies for high spirituality and enlightenment; teaching creativity, free and independent thinking; issues of respect for the elderly, respect for the young, promotion of a culture of public control in the community.